Climate Actions Transformative Mechanisms for Social Mobilisation - Delina, Laurence L.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Pivot, 2019)
"The climate movement is now old and robust enough to be studied--which in and of itself is good news. And the results of those inquiries are of great use in ... building this movement big enough and fast enough to catch up with the physics of global warming. This book will help make our labors more effective!" -Bill McKibben, founder, 350.org, and Schumann Distinguished Scholar in Environmental Studies, Middlebury College, USA "Addressing climate change will not be achieved through business as usual. ... To learn how citizen action might be improved, Laurence Delina brings to bear insights from social theory combined with reports from numerous action groups. ... Climate Actions offers a wealth of ideas and information for anyone seeking to make actions as effective as possible." -Brian Martin, Emeritus Professor, University of Wollongong, Australia Climate change remains a challenge that needs to be addressed at its core, particularly the rapid reduction of anthropogenic greenhouse gas emissions. This book discusses strategies for climate actions by synthesizing insights from a set of international 'contemporary social action group's' surveys. Based on these Delina introduces a synthesis of mechanisms for generating change, designed around 5 main themes: relationships (relating); value-based messages (messaging); alternatives (visioning); diversity (webbing); and communication (interacting). This book will be of great value to all academics and practitioners interested in the future development of our climate.
1 Introduction -- 2 Relating -- 3 Messaging -- 4 Visioning -- 5 Webbing -- 6 Interacting -- 7 Conclusion.
Keywords: Environment; Climatology; Human geography; Environmental Sciences; Climate Sciences; Human Geography